Implementasi Strategi Produk Dalam Keunggulan Bersaing - Reika Happy Sugiastuti; Irvan Kharisma Putra (Universitas Yudharta Pasuruan, 2019)
English This study aims to determine the implementation of product strategies in the competitive advantage of cake products in Malang Kendedes Cake & bakery. Qualitative research methods are used with a case study approach. And withdrawing data by dept interview from the informant by purposive sampling. The results of the study show: (1) The product strategy adopted by Citra is to develop new products (2) The competitive advantage in the image is to have product differences compared to competitors; (3) The constraints experienced by Citra are multuative marketing or in certain months, the solution is to strengthen sales estimates at each store Keywords: implementation of product strategies, competitive advantage, baking products Indonesia Penelitian ini bertujuan untuk mengetahui implementasi strategi produk dalam keunggulan bersaing produk kue di citra kendedes cake & bakery malang. Digunakan metode penelitian kualitatif dengan pendekatan studi kasus. Dan penarikan data dengan dept interview dari informan dengan cara purposive sampling. Hasil penelitian menun-jukkan: (1) Strategi produk yang diterapkan oleh Citra adalah dengan mengembangkan produk baru (2) Keunggulan bersaing di citra adalah dengan mempunyai perbedaan produk dibandingkan dengan para pesaing; (3) Kendala yang di alami oleh Citra adalah pemasaran multuatif atau pada bulan-bulan tertentu, solusinya adalah dengan memperkuat estimasi penjualan disetiap toko Keywords: implementasi strategi produk, keunggulan bersaing, produk kue